UJI PEMANFAATAN DAUN SIRSAK (Annona muricata L.) DALAM MENGHAMBAT STRES OKSIDATIF PADA TIKUS WISTAR HIPERKOLESTEROLEMIA MELALUI PENINGKATAN AKTIVITAS SUPEROXIDE DISMUTASE - Wahjuni, Sri; Santi, Sri Rahayu; Astuti Wulandari, Ni Nyoman (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015DO - 10.24843/JCHEM.2015.v09.i01.p11, 2015)
Oxidative stress is an imbalance condition between free radicals in the body with the anti-oxidant. Superoxide dismutase (SOD) is one of the endogenous anti-oxidant that can neutralize the excess of Reactive Oxygen Species (ROS). The excess of ROS that caused by stres oksidative can also be neutralized with the help of exogenous anti-oxidants. A soursop plant (Annona muricata L.) has anti-oxidant activity, especially in the leaves. This study aims to determine the activity of the leaves of the soursop (Annona muricata L.) in inhibiting the oxidative stress that conducted on the object hypercholesterolemic rats wistar through increasing SOD activity using variations of the extract dose of 50 mg/kg BW; 100 mg/kg BW and 150 mg/kg BW. In this study the dose gives the best result in inhibiting the oxidative stress through an increase in SOD activity was dose of 150 mg/kg BW with percent inhibition of SOD at (81,42% ± 3.91) where the percent inhibition of SOD is directly proportional to the activity of SOD
Keywords: soursop leave (Annona muricata L.), hypercholesterolemic, oxidative stress, SOD